The Koan: Texts and Contexts in Zen Buddhism. Edited by Steve Heine and Dale Wright. - Barrett, T. H. (Buddhist Studies Review, 2002)
The Koan: Texts and Contexts in Zen Buddhism. Edited by Steve Heine and Dale Wright. Oxford University Press, New York 2000. xii, 322 pp. £30.00 (hbk), 13.95 (pbk). ISBN (hbk) 0-19-511748-4, (pbk) 0-19-511749-2.